2017
DOI: 10.1063/1.4978910
|View full text |Cite
|
Sign up to set email alerts
|

Controlling shockwave dynamics using architecture in periodic porous materials

Abstract: Additive manufacturing (AM) is an attractive approach for the design and fabrication of structures capable of achieving controlled mechanical response of the underlying deformation mechanisms. While there are numerous examples illustrating how the quasi-static mechanical responses of polymer foams have been tailored by additive manufacturing, there is limited understanding of the response of these materials under shockwave compression. Dynamic compression experiments coupled with time-resolved X-ray imaging we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This has been addressed to a degree in recent publications by Hawreliak et al, 22 Winter et al, 23 and Branch et al, 24 whereby the dynamic compression response of lattices or other long-range periodic structures was elucidated. Studying the dynamic compression of such heterogenous open structures requires a more spatially resolved targeted diagnostic.…”
Section: Introductionmentioning
confidence: 99%
“…This has been addressed to a degree in recent publications by Hawreliak et al, 22 Winter et al, 23 and Branch et al, 24 whereby the dynamic compression response of lattices or other long-range periodic structures was elucidated. Studying the dynamic compression of such heterogenous open structures requires a more spatially resolved targeted diagnostic.…”
Section: Introductionmentioning
confidence: 99%
“…Cruttmann [ 64 ] used finite element simulations to find that cellular media mainly absorbed impact loads through internal cell deformation and collapse to attenuate stress waves. Branch [ 65 , 66 ] found that the periodically arranged cell structure [ 67 ] can adjust the elastoplasticity of a cellular medium. Cellular media materials with simple cubic structures were prone to stress concentration, which induced emission flow and attenuated impact load energy.…”
Section: Characterization Of Cellular Medium Mechanical Propertiesmentioning
confidence: 99%
“…Dattelbaum et al [248,249] developed the idea of 3D printing neoprene-like structures made of explosives to enhance or suppress hotspot formation. Compared to the traditional approach of controlling the mechanical sensitivity or susceptibility to detonation by changing the chemical structure (e. g., replacement of RDX with FOX-7), the considered approach is based on the variations in density and void size made during 3D printing while the chemical composition is unaltered.…”
Section: Progress In Additive Manufacturing Of Energetic Materialsmentioning
confidence: 99%